DEVELOPMENT OF INTERACTIVE VIDEO-ASSISTED WORKSHEETS: ENHANCING STUDENTS' VISUAL INTELLIGENCE - Rossie, Khalia; Dwiningsih, Kusumawati; Setiyanti, Aisha; Setiawan, Mohammad Wahyu (JURNAL EDUSCIENCE, 2025)
Purpose–Development of interactive videos assisted by worksheet to improve students' visual intelligence on hydrocarbon compound material which is said to be valid, practical, and effective.Methodology–This research is a type of quantitative research with the ADDIE research development model. Data was collected from validation data, student questionnaire sheets, observation sheets and pretest and posttest question sheets. Then the validation data was analyzed using a Likert scale to test validity, observation sheets and student response questionnaires were analyzed to test practicality, and pretest and posttest question sheets were analyzed using SPSS and N-Gain hypothesis tests to test effectiveness.Findings–The results of the study are interactive videos assisted by worksheet on hydrocarbon compound material to improve students' visual intelligence are suitable for use because they meet valid criteria with a median score of content validation, construct, and visual intelligence of 3 with a good category. The interactive video is effective because it has a Wilcoxon showed significant improvements in student understanding with N-Gain> 3 of 92.86% with a high category, and is said to be practical because it obtains a percentage of 98.9% with a good category.Contribution–Innovation in the development of learning media, namely interactive videos assisted by worksheet to improve students' visual intelligence.